2007
DOI: 10.1093/jxb/erm006
|View full text |Cite
|
Sign up to set email alerts
|

QTLs for shelf life in lettuce co-locate with those for leaf biophysical properties but not with those for leaf developmental traits

Abstract: Developmental and biophysical leaf characteristics that influence post-harvest shelf life in lettuce, an important leafy crop, have been examined. The traits were studied using 60 informative F9 recombinant inbed lines (RILs) derived from a cross between cultivated lettuce (Lactuca sativa cv. Salinas) and wild lettuce (L. serriola acc. UC96US23). Quantitative trait loci (QTLs) for shelf life co-located most closely with those for leaf biophysical properties such as plasticity, elasticity, and breakstrength, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
61
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 43 publications
6
61
0
Order By: Relevance
“…It has already been shown that RILs of the cross between cultivated L. sativa and wild L. serriola used in this study have differentiated root architecture (Johnson et al 2000), seed and seedling traits (Argyris et al 2005), and leaf biophysical and developmental traits (Zhang et al 2007). To our knowledge no classical or quantitative genetic data are available on the genetic basis of traits that differ between wild and cultivated lettuce: the available studies have mostly focussed on offspring fertility of different Lactuca species and among cultivars crosses (Thompson et al 1941;Lindqvist 1960a, b;Prince et al 1979;de Vries 1990).…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…It has already been shown that RILs of the cross between cultivated L. sativa and wild L. serriola used in this study have differentiated root architecture (Johnson et al 2000), seed and seedling traits (Argyris et al 2005), and leaf biophysical and developmental traits (Zhang et al 2007). To our knowledge no classical or quantitative genetic data are available on the genetic basis of traits that differ between wild and cultivated lettuce: the available studies have mostly focussed on offspring fertility of different Lactuca species and among cultivars crosses (Thompson et al 1941;Lindqvist 1960a, b;Prince et al 1979;de Vries 1990).…”
Section: Introductionmentioning
confidence: 67%
“…maps, it appears that regions overlap with those found by Zhang et al (2007) for leaf biophysical and developmental traits, such as leaf area (LG3) and absolute growth rate (LG7) although the exact map alignment is difficult due to limited marker overlap. Such clustering is consistent with either many linked genes and/or of few genes with major pleiotropic effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al (2007) identified strong negative correlations between discolouration and the plasticity and elasticity of leaf tissue, and a positive correlation with break strength, suggesting that subsequent discolouration may be related the ability of the lettuce tissue to deform in response to physical pressure. Not only may wound sites discolour, either during crop production or in storage, but the increased phenolic levels and enzyme activities produced in response to wounding may represent increased discolouration potential if apparently healthy material, damaged shortly before or during harvest, is later cut for prepared salad production.…”
Section: Physical Damagementioning
confidence: 96%
“…Although Wurr et al (2003) found no relationship between tissue strength or stiffness and discolouration, physical leaf properties such as break-strength, plasticity, elasticity and cell area have been correlated with shelf-life in a cross between L. sativa and L. serriola, suggesting lettuce types with small cells and strong cell walls have better shelf-life (Zhang et al 2007). This observation supports the suggestion that cellular integrity may be important in reducing discolouration and Wagstaff et al (2010) noted that shelf-life increased by up to 66% with a concomitant reduction in membrane permeability in transgenic lettuce plants expressing reduced levels of the enzyme xyloglucan endotransglucosylase/hydrolase, which is involved in regulating cell wall rigidity.…”
Section: Influence Of Geneticsmentioning
confidence: 99%